2006
DOI: 10.1002/pmic.200500360
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and comprehensive analysis of the extracellular and cell surface proteome of the human pathogenCorynebacterium diphtheriae

Abstract: Secreted proteins of the human pathogen Corynebacterium diphtheriae might be involved in important pathogen-host cell interactions. Here, we present the first systematic reference map of the extracellular and cell surface proteome fractions of the type strain C. diphtheriae C7s(-)tox-. The analysis window of 2-DE covered the pI range from 3 to 10 along with a MW range from 8 to 150 kDa. Computational analysis of the 2-D gels detected almost 150 protein spots in the extracellular proteome fraction and about 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 80 publications
(52 reference statements)
3
49
0
Order By: Relevance
“…Previous studies have revealed that various carbohydrate metabolism enzymes are commonly found on the surfaces of different bacterial species (47,(92)(93)(94)(95)(96)(97). Here we found that bile exposure caused several changes in the amounts of proteins related to carbohydrate metabolism in the surface-associated proteome of GG.…”
Section: Bile Affects Central Metabolic Processesmentioning
confidence: 50%
“…Previous studies have revealed that various carbohydrate metabolism enzymes are commonly found on the surfaces of different bacterial species (47,(92)(93)(94)(95)(96)(97). Here we found that bile exposure caused several changes in the amounts of proteins related to carbohydrate metabolism in the surface-associated proteome of GG.…”
Section: Bile Affects Central Metabolic Processesmentioning
confidence: 50%
“…In the post genomic era, the availability of more and more improved methods for analyzing bacterial sub-proteomes has shed light on complex physiological phenomena such as the protein secretion mechanisms, 1 energy metabolism, 2 quorum sensing, 3 moonlighting proteins, 4,5 parallel catabolic pathways, 6 environmental adaptation 7 and detoxification mechanisms related to stress. 8,9 The analysis of extracellular and envelope-enriched proteomes can also supply information about exported virulence factors 10,11 useful for developing suitable diagnostics and therapeutics 12 and for discovering new interesting targets for vaccine development and antimicrobial chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Other actinobacteria have been reported to secrete substantially more proteins. Roughly 50% of the extracellular proteins of Corynebacterium diphtheriae had signal peptides, and 75% of supernatant proteins had signal peptides in Streptomyces lividans (10,14). The low degree of protein secretion in Frankia could be related to the medium used.…”
Section: Resultsmentioning
confidence: 99%